Evaluation of Risk Management Maturity in the Czech Automotive Industry: Model and Methodology - Marek Čech; Martin Januška (Amfiteatru Economic)
This article provides a review of currently used risk maturity models to provide an overview of the assessment and diagnostics of risk management maturity in companies. The main research goal is to develop an entry-level easy-to-use diagnostic tool for enterprise-wide risk management maturity assessment tailored to Tier I suppliers of the automotive industry. In the first step, the questionnaire for self-evaluation was prepared with the help of a panel of experts using a synthesis of existing models suitable for use in the automotive industry. The risk maturity assessment model is then prepared using the Delphi method and the Likert scale for multi-criteria evaluation since the experts insisted on setting different weights for each criterion. Based on the results presented in the paper, a risk maturity self-evaluation tool in the form of a questionnaire was created for companies. Findings: The initial purpose of the research was to provide a review of the currently used risk maturity models, which led us to find more than 77 maturity models. The origin of risk maturity models can be credited to Hillson (1997) who built the first risk maturity model based on the capability maturity model from the IT sector. A significant research effort was put into the observation of hard and soft benefits of risk management. Based on the analysis of carefully chosen models, the new model was synthesized. The proposed model uses a selfevaluating easy-to-use questionnaire. The questionnaire consists of 24 attributes divided into 5 modules that were evaluated based on the 25 questions. All attributes were assessed on a 10-point Likert scale using the Delphi method conducted with the panel of experts. The outcome and purpose of the model is an entry-level diagnostics questionnaire of company risk management maturity tailored for Tier I suppliers of the automotive industry. Originality/value: As risk management is complex, maturity models provide companies with the ability to assess their situation and set strategic goals in the field of risk management. Tailoring a risk maturity model for the needs of the specific organization or industry sector has been recommended by researchers and industry practitioners in risk management (Antonucci, 2016; Kaplan and Mikes, 2016; Marks, 2015; MARSH, 2018; McKay, 2017)